Enhanced production of thermostable catalase for efficient gluconic acid biocatalysis - Huang, Jiang; Wang, Jun; He, Jinling; Wu, Yupeng; Chen, Lizhi; Zhou, Shuangzi; Bian, Yeyu; Li, Yangyuan (Frontiers in Sustainable Food Systems, 2024)
The demand for gluconic acid (GA) has risen recently, driven by its extensive applications in the food, healthcare, and construction industries. The biocatalysis of gluconic acid, facilitated by glucose oxidase and catalase, hinges on enzyme stability, significantly influencing catalytic efficiency. Nonetheless, catalase requires enhancements in thermal stability and activity to meet the requirements of practical applications. We evaluated ten catalases expressed in Aspergillus niger, ultimately selecting the catalase from the thermophilic fungus Thermoascus aurantiacus, labeled as TaCat, for its superior thermal stability and operational performance. We successfully obtained a strain with the highest catalase activity by optimizing signal peptides and overexpressing the crucial heme synthesis enzyme. Enzyme production reached an impressive 321,779.5 U/mL in a 50-L fermenter. We further characterized the enzymatic properties of the recombinant catalase, focusing on its thermostability. Simultaneously, we used AlphaFold2 for structural predictions and conducted in-depth analyses via accelerated molecular dynamics simulations. Our application studies confirmed the considerable advantages of TaCat in terms of GA production. In conclusion, TaCat, distinguished by its remarkable thermal stability and high activity, holds substantial potential for GA production.